How Ancient Were Vitruvius’ veteres architecti (De arch. 1. 1. 12–13)? - Egorova, Sofia (Hyperboreus, 2024)
The modern translations of the Vitruvian On Architecture 1. 1. 12 translate de veteribus architectis Pythius … ait as “one of the old architects Pythius … says”. Meanwhile, some considerations of the usage of the preposition de oﬀer an opportunity to understand it as concerning or about, the whole phrase being as follows: “That is why concerning the old architects Pythius – who designed brilliantly the temple of Athena in Priene – states in his work that an architect should be able to be <even> better in all kinds of art and science than those who reached with all diligence and practice an excellence in a single form of art”. Another argument is that the adjective vetus, as opposed to the closely related antiquus, means in Vitruvius not just ‘remote in chronology’, but ‘belonging to the concluded period’, ‘former’. Comparison with the passage 5. 3. 8 shows that the ancient architects mentioned here may be masters of the Classical or Archaic period, i.e. the predecessors of both Vitruvius and Pythius (4th cent. BCE).